Increasing undergraduate nursing students' cultural competence: an evaluation study - Wenjia Liu; Teresa E. Stone; Rosanna McMaster (BMC, 2018)
Abstract Background Cultural competence has become increasingly important for Chinese health professionals because of internationalization and the opening up of China to overseas visitors and business as well as a growing awareness of the needs of minority groups within China. This study aimed to evaluate a workshop designed to improve cultural competence among Chinese undergraduate nursing students. Methods A one-group pretest and posttest design was applied. The intervention was a one-day workshop based on transformative learning theory using a variety of teaching strategies. Forty undergraduate nursing students from a university in Wuhan, China selected by convenient sampling received the intervention. Data were collected before the intervention (T1), immediately after the intervention (T2), and 1 month (T3) and 3 months (T4) following the intervention through the Chinese version of Cultural Competence Inventory for Nurses (CCIN). A researcher-designed evaluation form including open-ended questions was also used. Results Participants' scores by CCIN increased significantly in the total score (p < .001) as well as the components of cultural awareness (p = .003), cultural knowledge (p < .001), cultural understanding (p = .007) and cultural skills (p < .001), but not in cultural respect. This improvement maintained at T3 and T4. Overall, participants were satisfied with the workshop, and the qualitative results supported the effects of this intervention. Conclusions The one-day workshop was effective in improving nursing students' cultural competence. Replication or further refinement of this workshop is recommended for future research among additional nursing students with diverse backgrounds.